2013
DOI: 10.1002/bmc.2906
|View full text |Cite
|
Sign up to set email alerts
|

Liquid chromatography–tandem mass spectrometric assay for aliskiren, a novel renin inhibitor in micro‐volumes of human plasma: a pharmacokinetic application in healthy South Indian male subjects

Abstract: This paper describes a simple, rapid and sensitive liquid chromatography/tandem mass spectrometry assay for the determination of aliskiren in human plasma using nevirapine as an internal standard. Analyte and the internal standard were extracted from 100 μL of human plasma via liquid-liquid extraction using tert-butyl methyl ether. The chromatographic separation was achieved on a C18 column using a mixture of acetonitrile and 0.1% formic acid (90:10, v/v) as the mobile phase at a flow rate of 0.9 mL/min. The c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
(20 reference statements)
0
4
0
Order By: Relevance
“…To the best of our knowledge, there are no methods for the simultaneous determination of ALS and HCTZ in human plasma. Reported procedures for the estimation of ALS either alone [22][23][24] or in combination with other antihypertensive drugs [20,25] have used protein precipitation (PP) with acetonitrile [20], liquid-liquid extraction (LLE) with methyl tert-butyl ether [22] or solid phase extraction (SPE) from human serum [23], urine [25] or saliva [24]. Thus, to develop a simple method, initial trials were performed using acetonitrile as protein precipitant as reported by Mannemala and Nagarajan [20].…”
Section: Optimization Of Extraction Processmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, there are no methods for the simultaneous determination of ALS and HCTZ in human plasma. Reported procedures for the estimation of ALS either alone [22][23][24] or in combination with other antihypertensive drugs [20,25] have used protein precipitation (PP) with acetonitrile [20], liquid-liquid extraction (LLE) with methyl tert-butyl ether [22] or solid phase extraction (SPE) from human serum [23], urine [25] or saliva [24]. Thus, to develop a simple method, initial trials were performed using acetonitrile as protein precipitant as reported by Mannemala and Nagarajan [20].…”
Section: Optimization Of Extraction Processmentioning
confidence: 99%
“…Several methods have been reported for the determination of ALS as an isolated sample or together with other antihypertensive drugs in more complicated matrices such as pharmaceutical formulations and biological fluids. These methods have been based on spectrophotometry [6][7][8], spectrofluorometry [9,10], electrophoresis [11,12], liquid chromatography (LC) [8,[13][14][15][16][17][18][19][20][21], LC-MS/MS [22][23][24][25] and UPLC-MS/MS [26]. Similarly, a number of analytical methods have been presented for the estimation of HCTZ as a single analyte [27] and in the presence of different antihypertensive agents [8,12,14,16,18,19,[28][29][30][31][32][33][34][35][36][37][38][39] in pharmaceutical preparations and biological matrices using spectrophotometry [29,32], capillary electrophoresis [28], HPTLC [30,…”
Section: Introductionmentioning
confidence: 99%
“…The dwell time for each transition was set at 200 ms. The product ion mass spectra of anagrelide are presented in Fig 2 . As previous publications have discussed the details of fragmentation patterns of nevirapine, 18 we are not presenting the data pertaining to this. The LC-MRM technique was chosen for the assay development due to its inherent selectivity and sensitivity.…”
Section: Mass Spectrometrymentioning
confidence: 99%
“…Many UV and HPLC methods for quantitative and qualitative analysis of these drugs have been reported individually for ALS and AML (Anandakumar and Jayamariappan, ; Bhatia et al ., ; Chitlange et al ., ; Dongre et al ., ; Feng et al ., ; Jothieswari et al ., ; Kumar, ; Mohammadi et al ., ; Nalwade et al ., ; Patil et al ., ; Rathee et al ., ; Salve et al ., ; Wrasse‐Sangoi et al ., ). However, an intensive literature search revealed the bioanalytical methods reported for determination of ALS (Adireddy et al ., ; Aydoğmuş et al ., ; Burckhardt et al ., ; Limoges et al ., ; Waldmeier et al ., ), AML (Bahrami and Mirzaeei, ; Bhatt et al ., ; Ma et al ., ; Tatar and Atmaca, ; Zarghi et al ., ), a combination of AML and HCTZ (El‐Gizawy et al ., ; Sharma and Pancholi, ) and a combination of ALS and HCTZ (Belal et al ., ). To the best of our knowledge there is no bioanalytical method available for the simultaneous determination of ALS and AML.…”
Section: Introductionmentioning
confidence: 99%